Harmony in Diversity: The Dynamics of Interfaith Families - Mochamad Taufiqurrachman; Agus Machfud Fauzi (Jurnal Sosiologi Agama Indonesia (JSAI), 2023)
In Indonesia, a nation characterized by its diverse religious landscape, the phenomenon of interfaith families provides a distinctive lens to comprehend religious coexistence. This investigation delves into how religious beliefs are shaped within interfaith families, scrutinizing the ways in which these households manage the intricacies of varying religious views. Utilizing qualitative research methodologies, the study zeroes in on four Indonesian families, each hailing from different religious backgrounds. The research method includes thorough interviews and observational techniques, aiming to unravel the nuances of religious observance, communication, and the resolution of conflicts within these families. The results highlight the critical roles of mutual respect, transparent communication, and a collective dedication to familial harmony in preserving a balanced atmosphere. Notwithstanding their religious disparities, these families demonstrate significant levels of tolerance and comprehension, allowing individual members to freely engage in their respective religious practices. This study accentuates the significance of embracing diversity and nurturing tolerance as fundamental factors for the harmonious coexistence of varied religions within a domestic framework. AbstrakDi Indonesia, negara yang ditandai oleh pluralitas agama, fenomena keluarga beda agama menawarkan konteks unik untuk memahami koeksistensi agama. Penelitian ini mengeksplorasi konstruksi kepercayaan agama dalam keluarga beda agama, mengkaji bagaimana keluarga-keluarga ini menavigasi kompleksitas perbedaan keyakinan agama. Menggunakan metode penelitian kualitatif, studi ini berfokus pada empat keluarga Indonesia dengan latar belakang agama yang beragam. Melalui wawancara mendalam dan observasi, penelitian ini menyelidiki dinamika praktik agama, komunikasi, dan resolusi konflik dalam keluarga tersebut. Temuan menunjukkan bahwa saling menghormati, komunikasi terbuka, dan komitmen bersama terhadap kesatuan keluarga sangat penting dalam menjaga harmoni. Meskipun ada perbedaan agama, keluarga menunjukkan tingkat toleransi dan pemahaman yang tinggi, dengan anggota keluarga bebas mempraktikkan keyakinan masing-masing. Studi ini menekankan pentingnya merangkul keragaman dan menumbuhkan toleransi sebagai elemen kunci dalam koeksistensi damai agama yang berbeda dalam satu keluarga.